2016
DOI: 10.1016/j.arabjc.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of one-pot three component reaction for the synthesis of N′-aryl-N-cyanoformamidines, essential precursors of formamidine pesticides family

Abstract: Efficient one-pot three component reaction of aniline derivatives with cyanoamide and triethyl orthoformate at reflux in toluene affords N 0 -aryl-N-cyanoformamidines in high yields just by the distillation of the azeotrope toluene/ethyl alcohol. Labelled d 9 -Amitraz is prepared by the application of this procedure in the synthesis of formamidine pesticides family. ª 2015 The Authors. Production and hosting by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The efficient three-component reaction of TEOF 1 with cyanoamide 63 and primary aromatic amines 16 at reflux in toluene provides N′-aryl-N-cyanoformamidines 74 in high yields (Scheme 20). It is reported that the reaction occurred in toluene as the selected solvent as it forms an azeotrope with the ethanol that can be eliminated from the system by distillation, permitting a fast and broad exchange of reagents [72]. A three-component, microwave-assisted reaction of TEOF 1 with a series of cyclic secondary amines 72 and 5-aminopyrazoles 70, was also developed by Dolzhenko et al [71] for the synthesis of the new N-pyrazolylformamidines 73 (Scheme 19).…”
Section: Scheme 19 Synthesis Of N-pyrazolylformamidines 73mentioning
confidence: 99%
“…The efficient three-component reaction of TEOF 1 with cyanoamide 63 and primary aromatic amines 16 at reflux in toluene provides N′-aryl-N-cyanoformamidines 74 in high yields (Scheme 20). It is reported that the reaction occurred in toluene as the selected solvent as it forms an azeotrope with the ethanol that can be eliminated from the system by distillation, permitting a fast and broad exchange of reagents [72]. A three-component, microwave-assisted reaction of TEOF 1 with a series of cyclic secondary amines 72 and 5-aminopyrazoles 70, was also developed by Dolzhenko et al [71] for the synthesis of the new N-pyrazolylformamidines 73 (Scheme 19).…”
Section: Scheme 19 Synthesis Of N-pyrazolylformamidines 73mentioning
confidence: 99%
“…Cyanoformamidines are important intermediates for asymmetric synthesis of formamidines that have been widely tested as pesticides . In a recent report sequential nucleophilic attack of amine and cyanoamide to TEOF contributed to the formation of N′ ‐aryl‐ N ‐cyanoformamidines. A wide range of aromatic amines comprising electron donating, as well as electron withdrawing groups showed compatibility with the reaction conditions, giving high yield of cyanoformamidines (Scheme ).…”
Section: Carbon‐carbon and Carbon‐heteroatom Bond Formation Reactionsmentioning
confidence: 99%
“…Subsequently, the reaction process was made easier by replacing the carboxylic acids with aldehydes, obtaining 2-substituted and 1,2-substituted benzimidazole derivatives. Numerous methods Considering the stability, catalytic activity and selectivity of MK10 tested in the synthesis reactions of bifunctionalized cyclopentenones [95] and our experience in developing environmental reactions for the synthesis of pharmaceutical azo-compounds [96][97][98][99][100], we present a new and selective synthetic method to obtain benzimidazole derivatives in a solvent-free reaction, testing MK10 as a heterogeneous catalyst.…”
Section: Introductionmentioning
confidence: 99%